Antimicrobial effect of Baccaurea angulata fruit extracts against human pathogenic microorganisms - Momand, Lailuma; Zakaria, Robaiza; Mikail, Maryam Abimbola; Kamal, Tara; Ibrahim, Muhammad; Abdul Wahab, Ridhwan (Merit Research Journals, 2014)
The research application for drugs and food supplements derived from plants extracts have increased in recent years. Plants extract and their constituents are recognized to be safe, either because of their traditional use without any documented detrimental impact or because of dedicated toxicological studies. The potential of higher plants as a source for new drugs is largely unexplored. Thus, a systematic investigation was undertaken to screen for antibacterial activity from Baccaurea angulata. Plant that belongs to the family is used as food as well as treatment of infectious diseases such as diarrhoea, skin infections and gonorrhoea. The anti-microbial activity of the B. angulata fruit extracts have revealed different antimicrobial properties, that vary between three parts (whole fruit, fruit skin, and berry), three solvents (methanol, ethanol and aqueous), using agar well diffusion, and microdilution methods and different pathogens (Streptococcus pneumoniae, Staphylococcus epidermidis, Klebsiella pneumoniae and Pseudomonas aeruginosa). The highest observed antimicrobial activity was in ethanol extract of fruit skin using agar well diffusion against S. pneumoniae. Among tested Gram negative bacteria, K. pneumoniae was the most susceptible bacterium which showed the highest bacteriostatic and bactericidal activity using microdilution method. All parts of fruit extracts poses the antimicrobial activities against all human pathogenic microorganisms used in this study.